An Inverse Kinematic Model for the 3-PRS Compliant Parallel Mechanism With Forward Causative Force - Junjie Wei; Hai Bi; Hong Yao; Fangxin Chen (IEEE Access, 2023)
The inverse kinematic model is an essential mathematical tool of the performance analysis and motion control for the parallel mechanism. A diversity of mathematical methods is used for inverse kinematic modelling. However, for compliant parallel mechanism, the direction of the causative force in the model is always disregarded in previous works, which leads to large deviation due to the force sensitivity of the flexure hinge. A straightforward index is proposed to quantitatively evaluate the deviation. A new approach presented in this paper try to overcome this shortcoming, by considering the forward causative force during the inverse kinematic modelling, which makes model realize less deviation and more practical in motion control. Compliant matrix method is adopted to analyze the deformation of the flexure hinge. The effectiveness of the proposed methodology is verified, based on a 3-PRS compliant parallel mechanism, with finite element analysis simulation. The proposed methodology can be employed and extended to a variety of compliant parallel mechanism.